Effectiveness of the pharmaceutical supply chain to clinics attached to Mafikeng Provincial Hospital - Mokgatlha, Moitsoadi Sarah (My University, 2013)
The study set out to investigate the factors that led to pharmaceutical outages in clinics attached to Mafikeng Provincial Hospital (MPH). An exploratory research design was adopted for this purpose and a survey that included respondents from Mmabatho Medical Stores (MMS), MPH, clinics attached to MPH and transporters was conducted to address a number of research questions. The findings are displayed in charts and tables. The findings show that there were constraints experienced at each and every one of the points of the entire pharmaceutical supply chain. However, it was established that the constraints could be minimised to improve on the supply chain. Measures for improvements in the management of pharmaceutical supply chain were recommended. It was concluded that the successful implementation of the recommended measures would minimise pharmaceutical supply shortages in clinics.
Thesis (MBA) North-West University, Mafikeng Campus, 2013